Long-Term Isoflurane Therapy for Refractory Bronchospasm Associated with Herpes Simplex Pneumonia in a Heart Transplant Patient. (30th November 2010) - Hornuss, C.; Firsching, M.; Dolch, M.; Martignoni, A.; Peraud, A.; Briegel, J.
Abstract : A 47-year-old man with a history of heart transplant was admitted after severe traumatic brain injury and seizures. During mechanical ventilation, the patient developed bronchospasm that severely compromised respiratory function that led to cardiac arrest. After resuscitation, application of isoflurane through the Anaesthetic Conserving Device (AnaConDa) in the ICU successfully treated bronchospasm, provided adequate sedation, and enabled appropriate ventilation and diagnostic bronchoscopy. A subsequent bronchoalveolar lavage revealed a high amount of Herpes simplex DNA. Herpes simplex pneumonia was diagnosed and treated with acyclovir. Isoflurane treatment was applied for twelve days total without side effects on renal and cerebral function. The patient recovered quickly after the termination of sedation. At discharge, he was fully awake without focal neurological deficiency and his long-term outcome was excellent. This case demonstrates that isoflurane is a treatment option in life-threatening cases of bronchospasm and a safe option for long-term sedation.